Uniqueness of limestone soil-forming substrate in the forest ecosystem classification - P. Šamonil (Journal of Forest Science, 2007)
The uniqueness of limestone soil-forming substrate was assessed with respect to the classification of forest ecosystems. 50 soil profiles from the Bohemian Karst were studied and the results were confronted with previously published works from other karst areas. The evaluation of soil profiles was based on a macroscopic description, on the results of chemical and physicochemical analyses, and on a micromorphological study. The carbonate bedrock was a cause of specific genesis of soils in these sites - both recent and relict ones (terrae calcis). However, it does not always condition the unique characteristics of these sites whose differentiation would call for an a priori special edaphic category. Unique geochemical characteristics of the substrate are modified on the gradient of advanced pedogenesis (Holocene up to mid-Pleistocene soils were assessed) by a very intensive soil-forming process connected with the impact of allochthonous, mostly aeolian material. Two possible approaches were designed for the classification of these sites: (i) wider conception - distinction of the basic edaphic category with small limitations for the quality of soil-forming substrate, (ii) narrower conception - limestone edaphic category with a number of limitations to distinguish this edaphic category.